2018
DOI: 10.1021/acsabm.8b00033
|View full text |Cite
|
Sign up to set email alerts
|

Various Biomaterials and Techniques for Improving Antibacterial Response

Abstract: The majority of failures in prosthetic implants and devices are caused by infections. Microbial infections are one of the major causes of these failures. The present article reviews various techniques such as modification in surface chemistry/composition and tailored structures (micro to nano) for improving the antibacterial response of prosthetic implants. In addition, the application of external stimulants such as magnetic and electric fields, as well as polarization, is recently realized as a fairly appeali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 200 publications
1
68
0
Order By: Relevance
“…The use of nanotechnology is a viable prospective that can be employed in order to address this issue effectively [7]. Nanomaterials based on metal ions, have an outstanding of cytotoxicity activity against bacteria, fungi and viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanotechnology is a viable prospective that can be employed in order to address this issue effectively [7]. Nanomaterials based on metal ions, have an outstanding of cytotoxicity activity against bacteria, fungi and viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The surface modification using HA-ZnO nanocomposite can reduce ions leaching from a metal alloy and prevents the bacteria colonization over a bioimplant surface (Figure 4c) [118]. The experimental investigation suggested that the number of bacterial colonies could be reduced to 13% from 50.45% when ZnO content was increased from 1.5% to 30% (wt) in a HA-ZnO nanocomposite.…”
Section: Surface Coating Using Zno-based Nanocompositementioning
confidence: 97%
“…Nanomaterials are the advanced materials that could be effectively utilized to improve the surface and bulk properties of orthopedic bioimplants. A class of nanomaterials in response to electric/magnetic fields or polarization exhibit anti-bacterial properties without affecting the surface chemistry of bioimplants [118]. Nanotechnologies could improve the antibacterial response of the prosthetic bioimplants, which include compositional modification, surface chemistry alteration, as well as the application of properly tuned external stimuli [7,118].…”
Section: Surface Modification Effectsmentioning
confidence: 99%
See 2 more Smart Citations